2019
DOI: 10.1080/13569775.2019.1693244
|View full text |Cite
|
Sign up to set email alerts
|

Conflict, contestation, and corruption reform: the political dynamics of the EITI in Indonesia

Abstract: We thank David Brown, Eve Warburton, two anonymous reviewers, and the Editor in Chief for their comments on an earlier draft of this paper. We also thank The Ford Foundation for funding the research through its support to Perkumpulan Prakarsa's project 'To promote tax and revenue transparency and reduce illicit financial flows in the extractive, plantation and manufacturing sectors in Indonesia'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…As the introduction already explained, global actors, especially the World Bank and the International Monetary Fund initially introduced the EITI to Indonesia. They managed to convince the initially hesitant Indonesian government to join the EITI, with the Presidential decree 26/2010 as the legal basis for implementing the EITI in Indonesia (Rosser & Kartika, 2019). This presidential regulation stipulated the establishment of the EITI‐Indonesia MSG, an EITI steering committee and an implementing team.…”
Section: Studying Social‐ecological Reflexivity In the Eitimentioning
confidence: 99%
See 2 more Smart Citations
“…As the introduction already explained, global actors, especially the World Bank and the International Monetary Fund initially introduced the EITI to Indonesia. They managed to convince the initially hesitant Indonesian government to join the EITI, with the Presidential decree 26/2010 as the legal basis for implementing the EITI in Indonesia (Rosser & Kartika, 2019). This presidential regulation stipulated the establishment of the EITI‐Indonesia MSG, an EITI steering committee and an implementing team.…”
Section: Studying Social‐ecological Reflexivity In the Eitimentioning
confidence: 99%
“…From the Scopus database we could only retrieve two journal articles specifically discussing EITI implementation in Indonesia 6 . Rosser and Kartika (2019) discuss the political dynamics and actor constellations within the EITI‐Indonesia and revealed that the commitment to EITI implementation is waning. Yanuardi et al (2021) analyse the effects of the EITI, focusing on three aspects of governance quality.…”
Section: Studying Social‐ecological Reflexivity In the Eitimentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesia makes an ideal case for exploring norm localisation dynamics in the extractive sector. It has adopted various global initiatives targeting transparency as part of broader good governance reforms – Indonesia being a key supporter of the Open Government Partnership (OGP) initiative, and having participated in the Extractive Industry Transparency Initiative (EITI) since mid‐2000 (see Rosser & Kartika, 2019; Soerjoatmodjo, Hanafi, & Triwibowo, 2014). At the same time, efforts to implement these global norms have encountered significant challenges in the context of Indonesia's newly democratised political system and the rise of populism 4…”
Section: Methodsmentioning
confidence: 99%
“…The Columbia Study came to be better known as a sociological model or approach. The sociological approach shows that there is an influence between sociological values attached to the individual that influences one's behavior in politics (Rosser & Kartika, 2020). Sociological values in the form of religion, social class, ethnicity, region, family tradition and others.…”
Section: Political and Election Behaviormentioning
confidence: 99%